MAIN ASPECTS OF TEACHING DISCIPLINE “PHARMACEUTICAL CHEMISTRY” AT THE PROFESSIONAL COLLEGE - Велика, Алла; Тураш, Микола; Кропельницька, Юлія (SWorldJournal, 2024)
In this article authors consider the main aspects of teaching and development of the curriculum on the discipline “Pharmaceutical Chemistry” for students of the specialty “Pharmacy, industrial pharmacy” according to the credit-module system at the profess